Mobile-Based Employee Attendance System Design Using the Rapid Application Development Method at the Universitas Muhammadiyah Jakarta - Nursodik Nursodik; Susanna Dwi Yulianti Kusuma (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2022)
Employee attendance is an important activity because it is related to employee productivity and is usually used as part of paying employee salaries. Therefore, recording employee attendance must be thorough, fast and accurate. Now, various types of employee attendance systems have developed, one of which uses fingerprints. The employee attendance system currently used by the University of Muhammadiyah Jakarta is attendance using fingerprints placed in every building or faculty. This system has drawbacks, namely the limited availability of fingerprint scanners, placement of presence tools far from the work location, and dependence on presence tools. So with these weaknesses, a mobile apps-based attendance system was built that uses GPS to make it easier for employees to make attendance while in the presence area or where they work. The method used in this research is Rapid Application Development. With this system, the attendance process and attendance data processing is easier and more efficient, helping to maximize the attendance data collection and processing process.